Transliminality: Comparing Mystical and Psychotic Experiences on Psycho-Phenomenological Grounds - Feise-Mahnkopp, Patricia (Open theology, 2020)
On a phenomenal level, no differences between the mystical and the initial sequence of psychotic experience are to be found. Both are characterized by transliminality (i.e., an experience of consciousness transcending both the psychophysical and the rational realms). However, the situation is different if we integrate psychodynamic implications before and after those experiences into the comparison. One difference on this level is that the mystical experience (if it meets sufficient ego stability) primarily offers personality-strengthening potential. In contrast, transliminality, which occurs in the course of psychotic experience (if it encounters insufficient ego-stability or a pronounced vulnerability), primarily offers personality-weakening potential. However, if the therapeutic process succeeds in setting ego-stabilizing impulses (or eliminating thought and affect disorders which are typical for psychoses of the schizophrenic spectrum), a conscious incorporation of the transliminal experience into the further therapeutic process proves to be helpful, too. The essential philosophical and therapeutic significance of the connections analyzed here are reflected on with the help of philosophical and psycho(patho)logical phenomenology, in particular with the writings of Husserl’s and Pfänder’s pupil Gerda Walther, combined with current theorems of responsive phenomenology. Walther’s insights into the (dys-)functionalities of ego-center ("Ichzentrum"), self ("Einbettung des Ichzentrums"), and basic essence ("Grundwesen") in mystical and psychotic experience, with respect to their (meta-)transcendental relationship with divine essence ("göttlicher Wesensgrund") provoke further research questions on the constitutive and therapeutic implications of transliminality in the context of mystical and psychotic experience.